ANALYSIS OF LEXICAL UNITS (NEOLOGISMS) USED IN “ENTREPRENEURSHIP” (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
In the current developing and Progressive Era, words are also being updated in their rhythm, filling in a new line of words. In particular, our language has grown sufficiently in the amount of new words that are used economically and in business. Neologisms related to the field of entrepreneurship are said to be new words that are being used and newly introduced in this area. Also, neologisms that are used within the framework of all spheres also arise through the means of various processes. Lexical units (neologisms) that have entered the field of Entrepreneurship are summarized in the following article.